Iatrogenic Aspergillus infection of the central nervous system in a pregnant woman - Lokuhetty, M. D. S.; Wijesinghe, Harshima D; Weerasundera, Buddhika; Dayapala, A (Medknow Publications - India, 2009)
A healthy postnatal woman succumbed to fulminant iatrogenic Aspergillus infection of the central nervous system, following accidental inoculation into the subarachnoid space at spinal anesthesia, during an outbreak of Aspergillus meningitis in Sri Lanka. Autopsy revealed extensive Aspergillus meningitis and culture confirmed Aspergillus fumigatus. The thalamic parenchyma in the brain was invaded by fungal hyphae producing necrotizing angitis with thrombosis, thalamic infarcts and fungal abscesses. The directional growth of fungal hyphae from the extra-luminal side of blood vessels towards the lumen favored extension from the brain parenchyma over hematogenous spread. The spinal parenchyma was resistant to fungal invasion in spite of the heavy growth within the spinal meninges and initial inoculation at spinal level. Modulation of the immune response in pregnancy with depression of selective aspects of cell-mediated immunity probably contributed to rapid spread within the subarachnoid space, to involve the brain parenchyma leading to clinical deterioration and death
Keywords: Aspergillus; central nervous system infections; latrogenic; postpartum